Pemberdayaan Masyarakat Melalui Edukasi Sosial, Literasi Keuangan, Literasi Digital, dan Digitalisasi UMKM di Desa Tambun - Adelia Selsabila Dewi Mungkas; Arta Uli Pangaribuan; Aurel Rizky Hanafi; Camelia Diva Kirani; Dhea Nabila Azzahra; Farhan Nasuha; Henry Afif Setiantono; Imelda Cantika Rizqina P; Matias Daeli; Nahdil Khoiru Hakim; Naila Shafa Salsabila; Nuria Fadilah; et al. (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2026)
Community service activities are one of the implementations of the Tri Dharma of Higher Education that aim to improve community welfare through educational and empowerment programs. This community service activity was conducted in Tambun Village, Bekasi Regency, through four main programs: anti-drug and anti-bullying education, financial literacy and saving culture education, healthy gadget usage education, and MSME digitalization assistance. The activity employed a participatory approach involving observation, socialization, mentoring, and evaluation. The target participants included junior high school students, elementary school students, parents, and local MSME actors. The results indicated an increase in participants' understanding of the dangers of drugs and juvenile delinquency, improved awareness of financial management from an early age, increased parental awareness regarding healthy gadget use, and enhanced understanding among MSME actors regarding digital marketing utilization. The implementation of these programs demonstrated that educational and mentoring approaches can contribute positively to community empowerment. In addition, students gained practical experience in communication, leadership, teamwork, and problem-solving within community settings.